2000
DOI: 10.1007/s004640010060
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of warmed insufflation carbon dioxide gas for laparoscopic cholecystectomy

Abstract: The use of carbon dioxide gas warmed to body temperature to produce a pneumoperitoneum during short-term laparoscopic surgery has no clinically important effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 11 publications
0
37
0
3
Order By: Relevance
“…Institute of Medical Sciences during the period of 16 months from June 2015 to September 2016, were enrolled out of which 3 patients were excluded from the study due to laparoscopic to open conversion because of intraoperative bleeding (1) and gallbladder adhesion (2). So a total of 97 patients (70 females, 27 males) were included in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Institute of Medical Sciences during the period of 16 months from June 2015 to September 2016, were enrolled out of which 3 patients were excluded from the study due to laparoscopic to open conversion because of intraoperative bleeding (1) and gallbladder adhesion (2). So a total of 97 patients (70 females, 27 males) were included in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Pain management has not been standardized at mass medical centers in India and abroad and this is reflected in the number of different pain studies after LC available in literature. Till day, many different methods have been used with conflicting rates of success to diminish the intensity of PO pain after LC [1][2][3][4][5][6][7][8][9]. They include low pressure pneumoperitoneum, gasless technique of LC, use of warm carbon dioxide, peritoneal wash with saline solution, strict surgical technique, perfect hemostasis, trocar site infiltration of anaesthetic drugs, instillation ofsubdiaphragmatic region with anaesthetic/analgesic drugs, or use of nonsteriodal anti-inflammatory drugs or dexamethasone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the thermodynamic losses from the abdominal cavity associated with humidifying the dry gas [5,13]. Randomized controlled clinical trials have not shown warm dry gas to significantly improve postoperative pain or core temperature compared to cold-dry CO 2 [33][34][35][36]. In fact, after laparoscopic fundoplication, Wills et al (2001) showed an increase in postoperative pain when warm dry CO 2 vs. cold-dry CO 2 was used [36].…”
Section: Warm Dry Co 2 Insufflationmentioning
confidence: 99%
“…The increase of living donors, due to the facility of video-assisted surgery associated with the use of marginal donors, has supported the importance of the problem of eventual deleterious effects of the pneumoperitoneum in these particular cases (Hazebroek et al, 2002 Nature and temperature of the gas used (Saad, Minor, Mohri, & Nagelschmidt, 2001;Farias et al, 2011;Berganza & Zhang, 2013), as well as the pressure (Berguer, Gutt, & Stiegmann, 1993), the speed of insufflations and maintenance, hemodynamic repercussions, and the eventual diffusion of microorganisms have been exhaustively studied (Sorbello et al, 2003).…”
Section: Introductionmentioning
confidence: 99%